Strategies for changing the nursing preceptorship activity in Primary Health Care - Juliana Andréa Duarte Araújo; Carine Vendruscolo; Edlamar Kátia Adamy; Leila Zanatta; Letícia de Lima Trindade; Daiana Kloh Khalaf (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to present actions to qualify preceptorship and teaching-health service integration to strengthen nursing training in PHC internship. Methods: qualitative research, developed through the Appreciative Inquiry Research carried out with eight nurses, both from the fields of teaching and health service, within Primary Health Care. The production and documentation of information took place between April and June 2019, through five meetings that characterized the four phases that make up the "4D cycle": Discovery, Dream, Design, and Destiny. Ethical issues were respected. Results: the participants dreamed of the best scenario for preceptorship and built a schedule of actions related to the qualification of preceptorship in Nursing and the strengthening of teaching-health service integration. Final Considerations: it is possible, through effective participation of the actors involved in teaching and practice, the collective development of goals and actions, aiming at the qualification of nursing education.